Influence of transcrystalline layer on finite element mesoscale modeling of polyamide 6 based single polymer laminate composites. (15th January 2020) - Tohidi, Shafagh D.; Rocha, Ana Maria; Dourado, N.; Rezazadeh, Mohammadali; Quyền, Nguyễn T.; Zille, Andrea; Hesseler, Stefan; Gries, Thomas; Dencheva, Nadya V.; Denchev, Zlatan
Abstract: This study presents a novel approach for finite element modeling of the elastic behavior of a plain-woven reinforced single polymer laminate composites (WSPC) based on polyamide 6 (PA6). These composites are produced via compression molding of PA6 woven textile structures that are powder-coated by anionic PA6 microparticles. Morphological and structural analysis complemented by electron microscopy, image processing and X-ray diffraction suggest the presence of transcrystalline layer (TCL) at the matrix-reinforcement interface. Having in mid this experimental fact, a novel procedure is developed for finite level discretization of TCL in the representative volume element (RVE) during tensile straining. The procedure correlates the material properties with the overall load applied, thus adequately modelling the tensile behavior of the WSPC based on the constituent materials. The stress field along the elements of the RVE model is studied while the tensile loads were applied in two principal directions. A good agreement between the real mechanical behavior and that calculated based on the model was demonstrated.